Hubungan Gaya Kepemimpinan Transformasional dengan Organizational Citizenship Behavior (OCB) pada Perawat di RSUD Panembahan Senopati Bantul Yogyakarta - Raden Jaka Sarwadhamana; Sumarni Sumarni; Nava Yuliandari (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
The rapid development of health can be seen from the increasing number of hospitals. The hospital is to be followed by the quality of human resources in supporting high-quality health services. This study aims to determine the relationship between transformational leadership style and organizational citizenship behavior (OCB). The approach used in this research is quantitative analytic approach with cross sectional study. The population and sample in this study were non-civil servant functional nurses in inpatient rooms class II and III at Panembahan Senopati Bantul Hospital with a total of 55 respondents. Then to analyze the data in this study using Kendall-Tau with the help of the SPSS application. The results showed that there was a significan relationship between transformational leadership style and organizational citizenship behavior (OCB), where the correlation coefficient (r) was 0.344 with Sig. 0.009 (p <0.05). The conclusion shows that there is a relationship between transformational leadership style and organizational citizenship behavior (OCB) on nurses in panembahan senopati hospital, Bantul Yogyakarta.